Understanding the Metabolic Profile of Macrophages During the Regenerative Process in Zebrafish - Paredes, Lais Cavalieri; Olsen Saraiva Camara, Niels; Braga, Tarcio Teodoro (Frontiers in Physiology, 2019)
In contrast to mammals, lower vertebrates, including zebrafish (Danio rerio), have the ability to regenerate damaged or lost tissues, such as the caudal fin, which makes them an ideal model for tissue and organ regeneration studies. Since several diseases involve the process of transition between fibrosis and tissue regeneration, it is necessary to attain a better understanding of these processes. It is known that the cells of the immune system, especially macrophages, play essential roles in regeneration by participating in the removal of cellular debris, release of pro- and anti-inflammatory factors, remodeling of components of the extracellular matrix and alteration of oxidative patterns during proliferation and angiogenesis. Immune cells undergo phenotypical and functional alterations throughout the healing process due to growth factors and cytokines that are produced in the tissue microenvironment. However, some aspects of the molecular mechanisms through which macrophages orchestrate the formation and regeneration of the blastema remain unclear. In the present review, we outline how macrophages orchestrate the regenerative process in zebrafish and give special attention to the redox balance in the context of tail regeneration.